Image Processing and Communications Challenges 9 9th International Conference, IP&C'2017 Bydgoszcz, Poland, September 2017, Proceedings - Choraś, Michał; Choraś, Ryszard S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Presenting a series of research papers on image processing and communications, this book not only provides a summary of currently available technologies but also outlines potential future solutions in these areas. Gathering the proceedings of the 9th International Conference on Image Processing and Communications (IP&C 2017), held in Bydgoszcz, Poland, on September 13-14, 2017, the book is divided into three parts. Part I addresses image processing, offering a comprehensive survey of different methods of image processing and discussing computer vision. In turn, Part II presents novel works in algorithms and methods and showcases formal and practical advances. Lastly, Part III examines networks, communications and a diverse range of applications.
Image processing -- Binary Line Oriented Histogram -- CT-SPECT Analyzer - a tool for CT and SPECT Data Fusion and Volumetric Visualization -- Image search enhanced by using external data sources and reasoning -- Linguistic Description of Images Based on Fuzzy Histograms -- Using toboggan segmentation in detection of centers and radius of cell nuclei -- Evaluation of the pre-processing methods in image-based palmprint biometrics -- On the way to perfect steganography -- PET waste clasiﬁcation method and Plastic Waste DataBase âĂŞ WaDaBa -- Algorithms and Methods -- Estimation of Geometrical Deformations of 3D Prints Using Local Cross-Correlation and Monte Carlo Sampling.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Telecommunication; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing; Communications Engineering, Networks